Optically Active Polyurethane/Silica Aerogel Coated Cotton Fabrics for Thermal Protection - Lin, Ling; Li, Ziyin; Mao, Haiyan; Li, Wenyao; Wang, Chaoxia (Frontiers in Materials, 2021)
Application of SiO2 aerogel in thermal protective clothing has been limited due to its brittle nature, ordinary mechanical properties, and poor film forming performance. This work is aimed to develop thermal protective cotton fabrics by coating blended OPU/SiO2 aerogel with enhanced mechanical properties and thermal protection performance. The OPU/SiO2 aerogel composites with different ratio were applied onto cotton fabrics by knife-coating. The morphology, chemical component, crystalline structure, thermal stability and compression strength were characterized by scanning electron microscopy (SEM), Fourier transfer Infrared spectroscopy (FTIR), X-ray diffraction (XRD), thermogravimetric analysis (TG) and compression test, respectively. Besides, the warmth retention performance and heat protection performance together with air and moisture permeability of the coated fabrics were studied. The results showed that OPU/SiO2 aerogel were successfully coated onto cotton fabrics with enhanced mechanical properties and thermal stability together with better film forming capacity. The heat transfer coefficient of the coated cotton fabrics was distinctly dropped due to the synergistic effect of OPU and SiO2 aerogel, which resulted in higher warmth retention. The OPU/SiO2 aerogel coated fabrics exhibited obvious heat insulation performance with its surface temperate almost 4 oC than the uncoated fabrics. This work demonstrates a new strategy of fabricating stronger thermal insulating textiles using OPU/SiO2 aerogel composites.